Memnaprash: A boon to sheep farmers for harnessing higher lamb weight - Kumar, Raj; Meena, Rang Lal; Gurjar, L R; Devi, Indu; Sahoo, Artabandhu; Rohilla, P P; Singh, S K (Indian Farming, 2019)
Sheep farmers earn their livelihood mostly by selling lambs as profitable enterprise. Many a time, lambs are undernourished due to deficit milk from the dam and multiple births (twins/triplets). In that scenario, lambs failed to attain the required body weight at weaning. Undernourished lambs are more prone to diseases and thus encounter increased morbidity and mortality. Therefore, sheep farmers face economic setback due to loss of lambs or due to the lower market price. ICAR-CSWRI, Avikanagar has developed Memnaprash - a liquid milk formula, which is reconstituted milk powder.